Multidimensional performance characteristics of talented youth judoka: Dynamic balance and coping skills relate to international competitive performance - Schoof, S.; Krabben, K.; Lojanica, M. B.; Pion, J.; Elferink-Gemser, M. T. (International Journal of Sports Science & Coaching, 2024)
Understanding of the multidimensional performance characteristics (MPCs) that underlie performance and distinguish athletes of varying performance levels are key for talent development programs. However, in the Olympic combat sport of judo, including MPCs in talent development research is still a recent approach. Hence, little is known about the MPCs of talented youth judoka. Therefore, this study aimed to determine differences in MPCs of talented youth (U18) judoka with varying levels of success in international competition, specified by sex and corrected for body weight. Fifty-two international level judoka (males: n = 28, age: 16.7 ± 0.9 and females: n = 24, age: 16.3 ± 0.9) participated. Multiple linear regressions were performed with performance level as the dependent variable. Performance level was defined as the win rate at international competitions in one competitive season. Anthropometrical (e.g., body height), physiological (e.g., dynamic balance), and psychological (e.g., coping skills) characteristics were used as independent variables. Results showed that win rate of females positively relates to dynamic balance and coping with adversity, and negatively relates to goal setting and mental preparation (R2 = .611, p < .001). Peaking under pressure positively relates to the win rate of males (R2 = .152, p < .05). The extent to which MPCs explain competition performance differs between sexes. However, for both sexes, coping skills seem to be important. Therefore, it is recommended that psychological characteristics are integrated in talent programs of youth judoka next to the judo-specific, physiological and/or technical-tactical trainings whilst taking in consideration the individual differences.